ACOX1 activates autophagy via the ROS/mTOR pathway to suppress proliferation and migration of colorectal cancer - Bo Shi; Junjie Chen; Haoran Guo; Xinyu Shi; Qingliang Tai; Guoliang Chen; Huihui Yao; Xiuwei Mi; Runze Zhong; Yang Lu; Yiyuan Zhao; Liang Sun; et al. (Scientific Reports)
Abstract Acyl-CoA oxidase 1 (ACOX1), a member of the acyl-coenzyme A oxidase family, is considered a crucial regulator whose dysregulation is implicated in the occurrence and progression of various cancers. This study aims to elucidate the impact of ACOX1 in CRC, shedding light on its potential as a therapeutic target. Through analysis of the GEO dataset, it was found that ACOX1 is significantly downregulated in colorectal cancer (CRC), and this lower expression level is associated with a worse prognosis. Additionally, in vitro as well as in vivo, ACOX1 overexpression dramatically reduced the proliferation and metastasis of CRC cells. Mass spectrometry revealed the crucial role of ACOX1 in fatty acid β-oxidation, as its overexpression led to a substantial increase in reactive oxygen species (ROS) derived from fatty acid β-oxidation. Further experiments demonstrated that ACOX1 overexpression, through modulation of fatty acid metabolism, increased ROS levels, reduced the phosphorylation activation of the key autophagy regulator mTOR, enhanced autophagy, and ultimately suppressed the growth and metastasis of CRC. In conclusions, ACOX1 expression is decreased in CRC. ACOX1 may regulate autophagy by reprogramming lipid metabolism to modulate the ROS/mTOR signaling pathway, consequently inhibiting the proliferation and migration of CRC.